Variation in paediatric hospital antibiotic guidelines in Europe. Issue 1 (28th September 2015) - Spyridis, N; Syridou, G; Goossens, H; Versporten, A; Kopsidas, J; Kourlaba, G; Bielicki, J; Drapier, N; Zaoutis, T; Tsolia, M; Sharland, M
Abstract : Objective: To assess the availability and source of guidelines for common infections in European paediatric hospitals and determine their content and characteristics. Design: Participating hospitals completed an online questionnaire on the availability and characteristics of antibiotic prescribing guidelines and on empirical antibiotic treatment including duration of therapy for 5 common infection syndromes: respiratory tract, urinary tract, skin and soft tissue, osteoarticular and sepsis in neonates and children. Results: 84 hospitals from 19 European countries participated in the survey of which 74 confirmed the existence of guidelines. Complete guidelines (existing guidelines for all requested infection syndromes) were reported by 20% of hospitals and the majority (71%) used a range of different sources. Guidelines most commonly available were those for urinary tract infection (UTI) (74%), neonatal sepsis (71%) and sepsis in children (65%). Penicillin and amoxicillin were the antibiotics most commonly recommended for respiratory tract infections (RTIs) (up to 76%), cephalosporin for UTI (up to 50%) and for skin and soft tissue infection (SSTI) and bone infection (20% and 30%, respectively). Antistaphylococcal penicillins were recommended for SSTIs and bone infections in 43% and 36%, respectively. Recommendations for neonatal sepsis included 20 different antibiotic combinations. Duration of therapy guidelines was mostly available for RTI and UTI (82%). A third of hospitals with guidelines for sepsis provided recommendations for length of therapy. Conclusions: Comprehensive antibiotic guideline recommendations are generally lacking from European paediatric hospitals. We documented multiple antibiotics and combinations for most infections. Considerable improvement in the quality of guidelines and their evidence base is required, linking empirical therapy to resistance rates.